2003
DOI: 10.1379/1466-1268(2003)008<0329:eohsph>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 32 (hemoxygenase-1) in the normal and inflamed human stomach and colon: an immunohistochemical study

Abstract: Heat shock protein 32 (Hsp32, hemoxygenase-1) is induced by reactive oxygen metabolites (ROM) and degrades heme leading to the formation of antioxidant bilirubin. Increased mucosal generation of ROM occurs in gastritis and inflammatory bowel disease. We aimed to assess mucosal expression of Hsp32 in normal stomach and colon and to test the hypothesis that disease-related differential expression occurs in inflamed tissue. Gastric body and antral mucosal biopsies were obtained from 33 patients comprising Helicob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 28 publications
(40 reference statements)
4
35
2
1
Order By: Relevance
“…Our data support other work that has shown that Immunohistochemical studies have demonstrated that HO-1 is expressed constitutively in normal gastric and colonic mucosa and its upregulation occurs in these tissues during inflammation or the healing phase of gastric ulcers [28,29] . In the present study, significant HO-1 induction following treatment with lansoprazole in endothelial cells and macrophages, as well as antioxidant protection occurred at a concentration of 30 µmol/L.…”
Section: Discussionsupporting
confidence: 92%
“…Our data support other work that has shown that Immunohistochemical studies have demonstrated that HO-1 is expressed constitutively in normal gastric and colonic mucosa and its upregulation occurs in these tissues during inflammation or the healing phase of gastric ulcers [28,29] . In the present study, significant HO-1 induction following treatment with lansoprazole in endothelial cells and macrophages, as well as antioxidant protection occurred at a concentration of 30 µmol/L.…”
Section: Discussionsupporting
confidence: 92%
“…Because some HSPs have been reported to be overexpressed in the intestinal tissues of IBD patients (19,20,23) and in an animal model of IBD (21)(22)(23). HSF1 and HSPs are thought to be involved in the pathogenesis of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is proposed that HO-1 serves as an adaptive mechanism to protect cells from oxidative stress (37). In this context, an increased expression of HO-1 has also been shown in pathophysiological states such as atherosclerosis (38), sepsis (39), Helicobacter pylori-positive and -negative gastritis, and ulcerative colitis (40); in these two last inflammatory diseases, HO-1 was immunodetected in superficial and cryptic epithelial cells. Additionally, the protective role of HO-1 has been demonstrated in experimental colitis in trinitrobenzene sulfonic acid and dextran sodium sulfate models (41,42), and in IL-10-deficient mice (43).…”
Section: Discussionmentioning
confidence: 99%